Advances in Targeted Therapy for Brain Metastases in Human Epidermal Growth Factor Receptor 2 (HER2)-Positive Breast Cancer: A Focus on ADCs and TKIs - Rao B; Huo P; Lu J; Huang W (Breast Cancer: Targets and Therapy)
Bin Rao, Peicheng Huo, Jieming Lu, Wenwen Huang Breast Surgery, Wuzhou Red Cross Hospital, Wuzhou City, Guangxi, 543002, People’s Republic of ChinaCorrespondence: Bin Rao, Wuzhou Red Cross Hospital, Wuzhou, People’s Republic of China, Tel +86-0774-3832882, Email raobing0001@163.comAim: Brain metastasis remains a significant therapeutic challenge in HER2-positive breast cancer, contributing to poor prognosis and limited treatment options. This review aims to summarize recent advancements in targeted therapies for brain metastasis in HER2-positive breast cancer, with a focus on the efficacy, mechanisms, and clinical implications of antibody-drug conjugates (ADCs) and tyrosine kinase inhibitors (TKIs).Methods: We conducted a comprehensive review of clinical trials, real-world studies, and preclinical research.Main Content: This review summarizes the latest clinical and preclinical evidence on targeted therapies for brain metastasis in HER2-positive breast cancer. Key therapies, including trastuzumab deruxtecan (T-DXd) and tucatinib, are discussed, with a focus on their mechanisms, efficacy, and ability to overcome the blood-brain barrier (BBB). Clinical trials such as HER2CLIMB and DESTINY-Breast03, as well as real-world studies, are highlighted to demonstrate the superior intracranial response rates and survival benefits of these therapies.Conclusion: ADCs and TKIs represent a paradigm shift in the management of brain metastases, offering new hope for patients with HER2-positive breast cancer. Future research should focus on optimizing combination therapies, exploring novel biomarkers, and addressing resistance mechanisms to further improve outcomes. This review underscores the importance of continued innovation in targeted therapies for brain metastasis.Keywords: breast cancer, targeted therapy, antibody-drug conjugates, ADCs, human epidermal growth factor receptor 2-positive, HER2-positive